2018
DOI: 10.3389/fmicb.2018.01701
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Bacteriophages Infecting Clinical Isolates of Clostridium difficile

Abstract: Clostridium difficile is recognized as a problematic pathogen, causing severe enteric diseases including antibiotic-associated diarrhea and pseudomembranous colitis. The emergence of antibiotic resistant C. difficile has driven a search for alternative anti-infection modalities. A promising strategy for controlling bacterial infection includes the use of bacteriophages and their gene products. Currently, knowledge of phages active against C. difficile is still relatively limited by the fact that the isolation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 68 publications
3
53
0
Order By: Relevance
“…1D) and decreased by only 0.57 and 0.24 log units at pH 3.0 and pH 4.0, respectively, compared with pH 7.5. Overall, phage JD032 virions were tolerant to wide pH ranges and high temperatures, which is similar to other C. difficile phages, such as HN10, HN16-1, HN16-2, and HN50 (25).…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…1D) and decreased by only 0.57 and 0.24 log units at pH 3.0 and pH 4.0, respectively, compared with pH 7.5. Overall, phage JD032 virions were tolerant to wide pH ranges and high temperatures, which is similar to other C. difficile phages, such as HN10, HN16-1, HN16-2, and HN50 (25).…”
Section: Resultsmentioning
confidence: 52%
“…Biological characteristics and bacteriolytic activity in vitro. The thermostability of phage JD032 was tested using 10 8 PFU/ml purified phage lysate that was subjected to different temperatures (4,25,37,45,50,55,60, and 65°C) for 1 h. To test pH stability, the purified phage lysate was incubated at different pH ranges from pH 2.0 to pH 11.0 for 1-h intervals. After incubation in a temperature-controlled water bath or pH-controlled environment, the phage activity was determined by a double-layer plating experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Attempts have also been made to isolate phages for control purposes, but the isolates obtained are of phages with lysogenic lifecycles ( Figure 1 ). These isolates were obtained from environmental and clinical samples, as well as by induction with mitomycin C or UV light [ 22 , 23 , 24 ]. Until 2018, 24 genomes of C. difficile phages were found in public databases, most of them belonging to the family Myoviridae [ 25 ].…”
Section: Bacteriophage Diversitymentioning
confidence: 99%
“…Since little is known about the pH stability of E. faecalis phages, we compared the pH stability of phage HEf13 with those of other Gram-positive bacteria phages. Phage HEf13 titers were not affected by incubation at pH 11 and remained at around 30% at pH 12 ( Figure 4B), whereas reported titers of other phages were almost completely abolished at pH 11 (Li and Zhang, 2014;Chen et al, 2016;Phothichaisri et al, 2018). These comparisons demonstrated that phage HEf13 is relatively more stable to high temperatures and strongly basic conditions than other phages.…”
Section: Discussionmentioning
confidence: 83%